Analisis Pengaruh Self-efficacy, Kapabilitas, dan Perilaku Kerja Inovatif terhadap Kinerja - Vera Berliana; Tutuk Ari Arsanti (Jurnal Maksipreneur, 2018)
The relative power of personal factors such as self-efficacy, capability, and innovative work behaviour in predicting performance was tested with 40 teachers through a survey. The variables’ measurements are adapted from Avallone et al., (2007), Menon and Kohli (1999), Jong and Hartog (2008), and Campbell (1990). Path analysis were used to test the hypotheses. Our findings showed that all of hypotheses were accepted. The hypotheses stated that innovative work behaviour as a mediator variable were accepted in this study.